Phantom pain - etiopathogenesis and treatment methods - Joanna Olszak; Karolina Zalewa; Lidia Bartoszek; Dominika Orłowska; Wojciech Kapłan; Mikołaj Poleszczuk; Anna Czuba; Karol Poleszczuk; Alicja Milewska (Journal of Education, Health and Sport)
Introduction and Purpose